2013
DOI: 10.1177/1367493513503587
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of parents and nurses of hospitalised infants requiring oxygen therapy for severe bronchiolitis

Abstract: Bronchiolitis is a major cause of children's admission to hospital. The study aim was to describe the experiences of parents who had, or nurses who cared for, a child admitted to hospital for severe bronchiolitis requiring oxygen therapy. A descriptive phenomenological approach was used to interview 12 mothers and 12 nurses. The findings were clustered into three domains: fear, parent-child interaction and technical caring. The mothers found the experience to be extremely frightening, based on their fear that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
6
11
0
Order By: Relevance
“…Emerging caregiver perspectives about bubble CPAP included fear arising from misconceptions about oxygen therapy, the tubes attached to the baby's nose, coffin-shaped baby cots and bubbling sounds made by the device. Our findings on parental fears related to the bubble CPAP machinery (bubbling water and tubes) add to global findings that also concluded that tubes, and coffin shaped beds caused anxiety and discomfort among mothers (Gondwe, Gombachika, & Majamanda, 2017;Cervantes, Feeley, & Lariviere, 2011;Peeler, Fulbrook, & Kildea, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Emerging caregiver perspectives about bubble CPAP included fear arising from misconceptions about oxygen therapy, the tubes attached to the baby's nose, coffin-shaped baby cots and bubbling sounds made by the device. Our findings on parental fears related to the bubble CPAP machinery (bubbling water and tubes) add to global findings that also concluded that tubes, and coffin shaped beds caused anxiety and discomfort among mothers (Gondwe, Gombachika, & Majamanda, 2017;Cervantes, Feeley, & Lariviere, 2011;Peeler, Fulbrook, & Kildea, 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Oxygen delivery methods create a barrier between a mother and an infant such that mothers are afraid to hold their babies, are unable to see their babies' faces, and skin-to-skin contact is interrupted. 4,5 Physical contact between mother and child is necessary to develop parentinfant bonding, facilitate infant brain development, reduce the level of pain and stress for the child, and reduce depression levels for mothers. 28,29 Furthermore, the caregivers reported that the tubing on bCPAP machines prevented contact between them and their children.…”
Section: Discussionmentioning
confidence: 99%
“…This was also found in studies done in Canada and Australia, where the equipment necessary for oxygen delivery was a major cause of fear among mothers, as they were worried that their children may be hurt and the sound that the machine produced was terrifying and overwhelming. 4,5 This suggests a need for healthcare providers to explain the treatment plan comprehensively, which may include benefits, risks, functions of the machine, and potential complications, as this will prepare caregivers psychologically and help them adapt better to the situation. This study revealed that caregivers received psychological support from healthcare workers, family members, and friends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found HFNC allowed them to hold their infant and on occasion breast feed, which allowed the mother a sense of connectedness. This has been explored in detail in the thesis by Peeler,195 however within paediatric literature there are no publications surrounding the patient or parent experience with HFNC use.…”
Section: Patient/parent Experiencementioning
confidence: 99%